Literatureat the library: arts instigating reading (Citizenship in Action: Extension and Culture Magazine, 2024)
This report is about one of the experiences of the extension project Café LiterArte: a cup of flavour and knowledge with erudiction, CampusVeranópolis of the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS). The action was developed in 2022 and seeked to entice the taste for reading short stories and perform presentations by high school students on Campus's library. The tale "A moça tecelã", by Marina Colasanti, was interpreted in an unique and diverse way, providing different types of learning to the group members. Furthermore, the performance was presented at 29ª Book Fair of Veranópolis and performed in 2023, to students of municipal schools of Veranópolis.
Keywords: reading; literature; art